A framework to analyze tax non-complince among corporations in Malaysia / Nor Azrina Mohd Yusof - Mohd Yusof, Nor Azrina (2018)
Tax non-compliance is a serious issue highlighted by most of the tax authorities around the world. The negative impact from tax non-compliance not only diminishes taxpayers’ confidence in the tax system; but it can affect the economic and social development. In Malaysia, although tax authorities have initiated tax audit regularly and impose tax penalties, the issue of tax non-compliance among corporations still persist. This study proposes a framework for studying corporate tax non-compliance in Malaysia using resolved audited corporate cases and by surveying tax auditors’ experience with tax noncompliance. This study proposes that penalty rate, audit frequency, financial performance, the use of tax agents, firm size and size of company’s auditor will have effect on corporate tax non-compliance. The developed conceptual model in this paper and future empirical findings using this model will hopefully contribute towards the efficiency and effectiveness of the Inland Revenue Board of Malaysia (IRBM) in detection and prevention tax noncompliance among taxpayers.